Power Balance Control in an AC/DC/AC Converter for Regenerative Braking in a Two-Voltage-Level Flywheel-Based Driveline. (4th September 2011) - Oliveira, Janaína G.; Lundin, Johan; Bernhoff, Hans
Abstract : The integration of a flywheel as a power handling can increase the energy storage capacity and reduce the number of battery charge/discharge cycles. Furthermore, the ability of recovering energy of the vehicle during breaking can increase the system efficiency. The flywheel-based all-electric driveline investigated here has its novelty in the use of a double-wound flywheel motor/generator, which divides the system in two different voltage levels, enhancing the efficiency of the electric driveline. The connection of two AC electrical machines (i.e., the flywheel and the wheel motor) with different and variable operation frequency is challenging. A power matching control applied to an AC/DC/AC converter has been implemented. The AC/DC/AC converter regenerates the electric power converted during braking to the flywheel machine, used here as power handling device. By controlling the power balance, the same hardware can be used for acceleration and braking, providing the reduction of harmonics and robust response. A simulation of the complete system during braking mode has been performed both in Matlab and Simulink, and their results have been compared. The functionality of the proposed control has been shown and discussed, with full regeneration achieved. A round-trip efficiency (wheel to wheel) higher than 80% has been obtained.